The impact of renal tubulointerstitial dysfunction on the early and long-term prognosis in chronic heart failure patients with preserved left ventricular ejection fraction - V. V. Syvolap; V. A. Lysenko (Patologìâ)
Aim. To study the dependence of the early-term (1 year) and long-term (5 years) prognosis in patients with chronic heart failure (CHF) of ischemic origin with preserved left ventricular ejection fraction (LVEF) depending on renal tubulointerstitial functional disorders.